2001
DOI: 10.1104/pp.125.2.711
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions between the Specialist HerbivoreManduca sexta (Lepidoptera, Sphingidae) and Its Natural Host Nicotiana attenuata. III. Fatty Acid-Amino Acid Conjugates in Herbivore Oral Secretions Are Necessary and Sufficient for Herbivore-Specific Plant Responses

Abstract: Feeding by the tobacco specialist Manduca sexta (Lepidoptera, Sphingidae) and application of larval oral secretions and regurgitant (R) to mechanical wounds are known to elicit: (a) a systemic release of mono-and sesquiterpenes, (b) a jasmonate burst, and (c) R-specific changes in transcript accumulation of putatively growth-and defense-related mRNAs in Nicotiana attenuata Torr. ex Wats. We identified several fatty acid-amino acid conjugates (FACs) in the R of M. sexta and the closely related species Manduca q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
498
5
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(524 citation statements)
references
References 29 publications
16
498
5
5
Order By: Relevance
“…Indirect plant defenses have been intensively studied since the late 1980s, and to date, this phenomenon has been reported in more than 23 plant species (see reviews in Vet and Dicke, 1992;Sabelis et al, 1999;Turlings and Wäckers, 2004). Studies on the mechanisms leading to the production of herbivore-induced plant volatiles have revealed the role of herbivore-specific elicitors (Mattiacci et al, 1995;Alborn et al, 1997;Halitschke et al, 2001). These elicitors can activate various signaling pathways in the plant, causing an up-regulation of a large array of defense-related genes through cross-talk and resulting in accumulation or release of defense chemicals (Kessler and Baldwin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect plant defenses have been intensively studied since the late 1980s, and to date, this phenomenon has been reported in more than 23 plant species (see reviews in Vet and Dicke, 1992;Sabelis et al, 1999;Turlings and Wäckers, 2004). Studies on the mechanisms leading to the production of herbivore-induced plant volatiles have revealed the role of herbivore-specific elicitors (Mattiacci et al, 1995;Alborn et al, 1997;Halitschke et al, 2001). These elicitors can activate various signaling pathways in the plant, causing an up-regulation of a large array of defense-related genes through cross-talk and resulting in accumulation or release of defense chemicals (Kessler and Baldwin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid-amino acid conjugates and related compounds 2,3) are also present in the oral secretions of other lepidopteran larvae. [4][5][6][7] Interestingly, recent studies have revealed that volicitin activated genes for the synthesis of terpenoids 8) and the nitrogen-containing metabolite indole in corn seedlings. 9) Fatty acid-amino acid conjugates in the oral secretions of two Manduca species elicited bursts in the production of jasmonic acid 5) and ethylene.…”
mentioning
confidence: 99%
“…9) Fatty acid-amino acid conjugates in the oral secretions of two Manduca species elicited bursts in the production of jasmonic acid 5) and ethylene. 5,10) These results clearly show that volicitin-related compounds evoked some plant defense responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soon afterwards, it was reported that caterpillar-damaged plants release considerable amounts of volatiles that are highly attractive to parasitic wasps [2]. Follow-up work has revealed a remarkable sophistication to the interactions, which were found to involve elicitors in the oral secretions of the herbivores [15][16][17][18] that trigger the systemic emission [19] of variable blends of de novo synthesized [20] volatiles. The induction of volatile emissions occurs not only in response to herbivore feeding on leaves but can also result from the deposition of insect eggs on plant parts [21] and from feeding by insect larvae on roots [22,23 ], again resulting in the attraction of the respective enemies that use the eggs or root feeders as food.…”
Section: The Role Of Hipvs In Indirect Plant Defencesmentioning
confidence: 99%